Exercise-diet intervention ameliorates but fails to fully reverse obesity-induced ovarian dysfunction: evidence spanning folliculogenesis to embryonic development - Chen Xinyan; Yu Ting; Zhang Xi; He Shangfan; Li Junwei; Zhu jiaqiao; Ju Huiming; Li Feng; Xue Tongmin (Journal of Ovarian Research)
Abstract Obesity, a globally prevalent chronic disease, disrupts systemic homeostasis and impairs female fertility, yet the mechanisms linking adipose dysfunction to ovarian reserve remain unclear. Using high-fat diet-induced obese C57BL/6 mouse models (HFD) and exercise-diet intervention models (SE group), we systematically evaluated obesity-associated reproductive deficits. Histomorphological analysis revealed that HFD mice exhibited ovarian atrophy, increased atretic follicles, and reduced primordial/antral follicle counts, which were partially restored by SE intervention. TEM demonstrated lipid droplet accumulation and mitochondrial heterogeneity in HFD ovaries, with residual vacuolization persisting despite SE-mediated improvement. Superovulation assays demonstrated reduced oocyte production in HFD mice, accompanied by impaired in vivo maturation and blastocyst formation. Immunofluorescence revealed abnormal spindle assembly and heterogeneous mitochondrial distribution in HFD oocytes, potentially associated with elevated ROS. Mechanistically, HFD downregulated folliculogenesis regulators (BMP-15, HIF-1α, PTEN/AKT/FoxO3) while upregulating metabolic stress markers (Chemerin, CMKLR1). Western blot confirmed reduced ovarian protein acetylation and BMP-15/HIF-1α expression in HFD mice, with partial recovery following exercise-diet intervention. These findings demonstrate obesity-induced dual impairments: mitochondrial-ROS dysfunction compromising oocyte competence and BMP-15/HIF-1α suppression disrupting follicular survival through PTEN-AKT-FoxO3 signaling. Although exercise-diet intervention improved metabolic parameters and oocyte quality, residual abnormalities highlighted irreversible impairments. Our study identifies obesity as a driver of ovarian aging and emphasizes the fertility-enhancing potential of combined exercise-diet intervention in obese female mice.